2012
DOI: 10.1017/s0950268812000465
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and population structure of Staphylococcus aureus nasal carriage in healthcare workers in a general population. The Tromsø Staph and Skin Study

Abstract: SUMMARYHealthcare workers (HCWs) may be a reservoir for Staphylococcus aureus transmission to patients. We examined whether HCW status is associated with S. aureus nasal carriage and population structure (spa types) in 1302 women (334 HCWs) and 977 men (71 HCWs) aged 30–69 years participating in the population-based Tromsø Study in 2007–2008. Multivariable logistic regression models were used. While no methicillin-resistant S. aureus (MRSA) was isolated, overall, 26·2% of HCWs and 26·0% of non-HCWs were S. aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 30 publications
(42 reference statements)
6
32
1
5
Order By: Relevance
“…The study demonstrating this correlation was, however, larger than ours. A significant association between HCWs and a specific spa type (t160) was identified in paper IV, which is in line with a previous study, which, however, identified an association between two other spa types, namely t012 and t015, and HCWs (Olsen et al 2013). t160 was also the most common spa type in nursing homes in the same geographical area as the studies in papers III and IV (Stark et al 2014).…”
Section: Spa Type Distribution and Cluster Analysis (Papers III And Iv)supporting
confidence: 89%
See 2 more Smart Citations
“…The study demonstrating this correlation was, however, larger than ours. A significant association between HCWs and a specific spa type (t160) was identified in paper IV, which is in line with a previous study, which, however, identified an association between two other spa types, namely t012 and t015, and HCWs (Olsen et al 2013). t160 was also the most common spa type in nursing homes in the same geographical area as the studies in papers III and IV (Stark et al 2014).…”
Section: Spa Type Distribution and Cluster Analysis (Papers III And Iv)supporting
confidence: 89%
“…A thorough review of 18 studies from 1944 until 1994 showed that the mean S. aureus carriage rate in the general population was 37 % (Kluytmans et al 1997). More recent studies have shown nasal colonization rates of 20 % to 30 % (Andersen et al 2012;Gamblin et al 2013;Mernelius et al 2013b;Olsen et al 2013;Mehraj et al 2014). Nasal colonization rates of up to nearly 60 % have been reported among HIV-positive patients (Kotpal et al 2014), patients on hemodialysis (Duran et al 2006), intravenous drug addicts and patients with insulin dependent diabetes (Kluytmans et al 1997).…”
Section: Carriage and Colonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dulon et al (2014) asseguram que o risco do pessoal de Enfermagem ser colonizado com MRSA é quase duas vezes maior do que para o pessoal médico e três vezes maior do que para outros profissionais de saúde. Esse fato é assegurado tendo em vista que o transporte nasal de MRSA em profissionais de Enfermagem é mais elevado do que em outros profissionais da saúde, tendo em vista que o profissional de Enfermagem desempenha suas atividades cotidianas diretamente relacionadas ao paciente (OLSEN et al, 2013). Rongpharpi et al (2013) diante do quadro da colonização por S. aureus assinalam que dentre os fatores de prevenção de infecções relacionadas à assistência a saúde -IRAS, está o cumprimento de medidas sanitárias e Em relação aos colaboradores colonizados por MSSA, a maior parte era do gênero feminino, assim como o visualizado com os portadores de MRSA.…”
Section: Artigos Originaisunclassified
“…Em função desse conhecimento, torna-se fundamental a investigação quanto à identificação da prevalência e avaliação do perfil de sensibilidade de amostras em profissionais da área de saúde que prestam cuidados direto ao paciente, particularmente os profissionais da Enfermagem, visando assegurar impacto positivo na assistência, bem como desenvolver o conhecimento sobre grupos de alto risco (MOREIRA et al, 2013;MOURA et al, 2011;OLSEN et al, 2013). Diante da magnitude do quadro apresentado, o presente trabalho buscou avaliar a prevalência de Staphylococcus aureus resistente à meticilina (MRSA) nas mãos e mucosa nasal de profissionais de Enfermagem de um hospital da cidade de Cascavel, Paraná, Brasil.…”
unclassified